The Effect of Earthquake Disaster Triage Simulation Using Tabletop Media on Knowledge Among Nursing Students - Babang, Putri Sonia Rambu; Metrikayanto, Wahyu Dini; Choeron, Rachmat Chusnul; Sutriningsih, Ani; Ardiyani, Vita Maryah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Understanding earthquake disaster triage is a crucial component of the nursing curriculum, necessitating enhance educational efforts to improve triage knowledge through innovative learning methods. This study aims to investigate the effect of earthquake disaster triage simulation using tabletop media on the knowledge of nursing students at UNITRI Malang. Utilizing a one-group pretest -posttest design, the research involved all nursing students from the class of 2022 at UNITRI Malang. A sample of 35 students was selected through a simple random sampling technique. Data collection was executed using a structured questionnaire assessing knowledge on earthquake disaster triage, and analysis was performed using the marginal homogeneity test with α significant level of α = 0.05. Findings revealed that a majority of the respondents had poor knowledge of earthquake disaster triage before the tabletop simulation (57.1%), which significantly improved to a good category after the simulation (62.9%). The results indicated a significant effect of tabletop earthquake triage simulation on the knowledge of nursing students, with a p-value of 0.000. The tabletop simulation media can be an effective tool for enhancing knowledge in earthquake disaster triage.